As bailadeiras: Devadasis, dança e colonialidade na Índia portuguesa - século XVIII: no corpo iconografado uma categoria histórica - Silva, Jorge Lúzio Matos (2016)
The colonial system implemented by Portugal over the occupied territories in the west coast of India between the Sixteenth and Eighteenth centuries, by portraying the figure of the bailadeira, a category of dancer women associated with Hindu temples and whose representation had been based on reductionisms, misconceptions, and distortions related to prostitution, imposed an interpretation developed under the European ethnocentrism. It was a strategy to disqualify the local culture, facilitating the conquer project and the conversion to Christianity. Since the Indian antiquity, as observed in the bodies represented iconographically in ivory, the bailadeiras, particularly the devadasis, were the main carrier of their ancestry, religiously revived in the arts of liturgical dances and chants. Due to their social autonomy, these women transited in the spheres of the local power, always surrounded by ambivalences and contradictions from the colonial society. As historical subjects, they remained under stigma derived from the orientalism. This work, founded upon the Postcolonial Theory, aims to analyze the Indian coloniality and its mechanisms of self-affirmation and domination, which involves the bailadeira from the Portuguese India